Impact of exercise and leucine-enriched protein supplementation on physical function, body composition, and inflammation in pre-frail older adults: a quasi-experimental study - Merchant, Reshma Aziz; Chan, Yiong Huak; Anbarasan, Denishkrshna; Seetharaman, Santhosh; Au, Lydia; Nachammai, Vidhya; Lai, Alexa; Ho, Vanda; Wong, Beatrix Ling Ling; Pang, Eunice; Bhaskaran, Kalpana (Frontiers in Medicine, 2023)
Background Exercise and a protein-enriched diet are essential for muscle protein synthesis, cellular growth, mitochondrial function, and immune function. The U.S. Food and Nutrition Board's current guideline on recommended dietary allowance for protein in older adults is 0.8 g/kg per day, which may not be sufficient in vulnerable pre-frail older adults. Aims This study aimed to evaluate the impact of leucine-enriched protein supplementation with or without exercise over 3 months in pre-frail older adults who consumed ≤1 g/kg/day of protein on improving (i) physical function, (ii) body composition measures, and (iii) inflammatory biomarkers such as interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF-α). Methods A non-randomized cluster quasi-experimental study guided by the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) checklist of 178 pre-frail older adults [112 control, 44 nutrition (Nu), and 22 in the nutrition with exercise (Nu+Ex) group] comparing the effect of Nu+Ex and Nu on physical function, body composition, and inflammation. At 0, 3, and 6 months, questionnaires on demographics, depression, perceived health, and cognition were administered. Physical function assessment (short physical performance battery [SPPB] test, gait speed, handgrip strength, 5× sit-to-stand [STS]) was conducted, and body composition analysis was performed using a bioelectrical impedance analysis machine. IL-6 and TNF-α were measured at 0 and 3 months. Results At 3 months, there were significant improvements in gait speed, 5× STS, SPPB scores, depression, perceived health, fat-free mass, and appendicular skeletal muscle mass indices in the Nu+Ex group. Both Nu+Ex and Nu groups had improvements in body cell mass and reductions in IL-6 and TNF-α. The improvements were not sustained after 6 months. Conclusion Our study results need to be validated in future longitudinal randomized studies with a larger sample size focusing on populations at risk.